Keautentikan Akta PPAT Elektronik dan Tanggung Jawab PPAT dalam Perlindungan Data Pribadi - Nabilla Lintang Primarini; Muh. Afif Mahfud (Jurnal Hukum Lex Generalis, 2026)
Digital transformation in Indonesia’s land sector encourages implementation of electronic PPAT deeds under Government Regulation Number 18 of 2021. This policy creates juridical issues concerning deed authenticity and PPAT responsibility as personal data controllers under the Personal Data Protection Law. This study analyzes the legal position of electronic PPAT deeds, PPAT responsibilities and regulatory synchronization within electronic land administration. The research applies a normative juridical method using statute, conceptual and comparative approaches. Results indicate that electronic PPAT deeds do not fully satisfy authentic deed requirements under the ITE Law. Furthermore, PPATs must ensure personal data security, privacy protection and certainty.